2021
DOI: 10.1002/eat.23514
|View full text |Cite
|
Sign up to set email alerts
|

The costs and benefits of intensive day treatment programs and outpatient treatments for eating disorders: An idea worth researching

Abstract: Outpatient care (e.g., individual, group, or self‐help therapies) and day treatment programs (DTPs) are common and effective treatments for adults with eating disorders. Compared to outpatient care, DTPs have additional expenses and could have unintended iatrogenic effects (e.g., may create an overly protective environment that undermines self‐efficacy). However, these potential downsides may be offset if DTPs are shown to have advantages over outpatient care. To explore this question, our team conducted a sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…While we did not make directional hypotheses, previous evaluations of ED treatment which included DPs [26] showed that greater support for patient autonomy increased the motivation of patients, which leads to better outcomes. Extrapolation from the critique offered by Ali and colleagues [13] would also suggest that such changes might enhance outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While we did not make directional hypotheses, previous evaluations of ED treatment which included DPs [26] showed that greater support for patient autonomy increased the motivation of patients, which leads to better outcomes. Extrapolation from the critique offered by Ali and colleagues [13] would also suggest that such changes might enhance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, outcomes can be more confidently attributed to the treatment formats provided. In the future, it would be valuable to compare the outcomes of the DP in the current study to inpatient and outpatient treatments, as it has been consistently identified in the literature that there is limited research on clinical outcomes and, in particular, comparisons of different intensities of treatment [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should compare day-hospital CBT-E with "treatment as usual" to assess the true efficacy of the former. Furthermore, to test less expensive forms of stepped care approaches, as suggested by Ali et al (2021), non-responders to outpatient treatment could be randomized to day-hospital or treatment conclusion with the option to return to outpatient care when their motivation to change improves. However, according to our results, day-hospital CBT-E seems a promising alternative to inpatient treatment for patients with eating disorders not responding to outpatient treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Supportive Psychotherapy), far fewer studies have examined whether and when to provide treatment in the form of intensive day treatment versus outpatient treatment. In their Spotlight focused on these two most commonly employed in‐person delivery formats, Ali et al (2021) make the case that while the extant literature suggests that either format is clinically effective in improving outcomes in adult patients, the field is lacking cost‐effectiveness studies. Comparative studies are needed to test whether the greater costs of day treatment (e.g., due to direct costs related to the increased staff involvement, more extensive infrastructure, and indirect costs related to patients spending more time away from school, work or family duties) can be justified based on potentially superior patient outcomes (e.g., higher percent of patients who recover; shorter time to recovery; lower rates of relapse; etc.).…”
Section: Evaluating the Benefits Of Intensive Day Treatment Versus Ou...mentioning
confidence: 99%